Pengaruh Perencanaan Pembangunan Era Orde Lama pada Kesejahteraan Masyarakat Indonesia - Ananta Daru Pratiwi; Alifia Maulina; Aldilla Amalia; M.Fahza Rahmadi Rega; Ahmad Agil Surya R. (Journal of Economics Development Issues, 2023)
The reign of Indonesia's Old Order lasted for about 23 years, from 1945 to 1968 under the leadership of President Soekarno. The economic situation in the early days of independence (1945-1949) was quite bad, including various problems such as very high inflation, the Dutch economic cessation since November 1945, and massive exploitation during the colonial period. However, during the old order, President Soekarno had a development strategy based on this development plan. This development plan put more emphasis on political development efforts where at that time the government was trying to maintain national independence. In 1947 the government started planning by making a Three-Year Production Plan for the Republic of Indonesia in 1948, 1949, and 1950. This program focused on agriculture, animal husbandry, industry, forestry, and other programs.